Effect of Spices on Improving the Stability of Frozen Stored Fish Mince - Joseph, Jose; George, Chinnamma; P.A., Perigreen (Fishery Technology, 2025)
The frozen storage characteristics of minced fish incorporated with different concentrations of clove, cinnamon and pepper were studied. Clove was found to have strong antioxidant effect. As the concentration of the spices increased a proportional increase in the frozen storage stability was noticed. Higher concentrations of clove and pepper (0.2%) were not appreciated by the taste panel. No consistent and concordant TBA values were obtained for samples incorporated with cinnamon and pepper while clove gave good results